Nation state formation in Malaysia (1945-1974) - Mohd. Ashraf Ibrahim (Penerbit UKM, 2010)
The aim of this research is to discuss the process of a nation state formation by the British colonial government after the Second World War (1945) until the formation of the National Front Party (1974). This research begins by examining the British government's effort to create a united Malayan nation through the policy of common citizenship and education. The formation of the Malayan constitution then by the Reid Commission had formed the concrete basis for nation building after the country achieved its independence in 1957. This research examines the challenges and obstacles faced by the government in realizing the constitutional spirit in order to create a just and fair nation state. Among the earliest challenges and obstacles in the effort of nation state building was the fact that the inhabitants had different understanding and sometimes contesting nation of intent. In this context, this research looks at several aspects such as education, language and economics. Although the government faced difficulties to implement Article 152 and Article 153, the citizenship issues had been overcome successfully indeed. The challenges faced by Malaysia with the entry of Sabah, Sarawak and Singapore (1963) were given special attention, particularly over the issue of a Malaysian Malaysia and multilingualism. The May 13 incident and the effort to build "a new Malaysia" through the implementation of the New Economic Policy and the politics of consensus were also the main themes for this research. Besides using related secondary sources, this research had relied on the primary sources such as official reports from the Colonial Office (CO), the Foreign and Commonwealth Office (FCO), the Prime Minister's Office (PREM) and the British Cabinet (CAB) from the National Archives in London. Official and private records that were kept at the National Archives, Malaysia were also used as references. This research found that the nation state built by the British was a concept imposed on the inhabitants of this country and therefore was artificial in nature. Consequently, Malaysia had faced problems in forming a strong nation after independence. Language, education and economy were still the main issues. The political situation had become more complicated because of the demands made by the opposition parties, especially by the PAP and DAP for the amendment of Article 152 and 153 to pave the way for a Malaysian Malaysia state. The climax of the debate and disputes were the separation of Singapore in August 1965 and the infamous May 13 racial riot in 1969. The introduction of the New Economic Policy and the politics of consensus were the efforts initiated by the government to overcome problems that were hindering the success of the development of a nation state.